2004
DOI: 10.1002/app.20852
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the tensile behavior of fiber bundles with irregular constituent fibers

Abstract: In this paper, the effect of fiber dimensional irregularities on the tensile behavior of fiber bundles is modeled, using the finite element method (FEM). Fiber dimensional irregularities are simulated with sine waves of different magnitude. The specific stress-strain curves of fiber bundles and the constituent single fibers are obtained and compared. The results indicate that fiber diameter irregularity along fiber length has a significant effect on the tensile behavior of the fiber bundle. For a bundle of uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This was done using a Single Fibre Analyser (SIFAN). The importance of within-fibre diameter variations on fibre mechanical properties has been examined in the literature (He & Wang, 2004 Ignoring the within-fibre variability may underestimate yarn limiting irregularity as well as effective fineness. This study examines how within-fibre diameter variation affects yarn limiting irregularity and effective fineness.…”
Section: ) ( Lim Yarn CV Amentioning
confidence: 99%
“…This was done using a Single Fibre Analyser (SIFAN). The importance of within-fibre diameter variations on fibre mechanical properties has been examined in the literature (He & Wang, 2004 Ignoring the within-fibre variability may underestimate yarn limiting irregularity as well as effective fineness. This study examines how within-fibre diameter variation affects yarn limiting irregularity and effective fineness.…”
Section: ) ( Lim Yarn CV Amentioning
confidence: 99%
“…Results of testing and analyzing woven fabric samples showed that instead of linear fiber elements, nonlinear elements had to be used for modeling tensile behavior (Vas et al 2013 ). The use of such type of bundles can be found in some papers dealing with other structures as well (Goh et al 2013 ; He and Wang 2004 ). We had similar results when testing biological (plant, animal, and human) tissues (Hangody et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%